The Psychological Effects Of Coronavirus (COVID-19) Outbreaks On A Sample Of Syrian Society - سعدي, ريما; صقور, سام; محمد, هلا (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The aim of the current research is to identify the psychological effects of the Coronavirus outbreak on Syrian society. The research sample consisted of (438) individuals who answered the tests electronically through the internet at the end of the third week of the Syrian government taking precautionary measures to prevent the spread of the virus. The DASS-21 scale was used to measure the level of depression, anxiety and stress, the IES-R scale was used to measure the level of psychological impact of the traumatic event. The focus was on variables (gender, age, place of residence, educational, social, and professional level). The results showed that there were different levels of depression in half of the sample (50%), their levels ranged between (mild 17.4%, moderate 29.5%, extremely severe 3.2%), and different levels of anxiety in about a third of the sample (33.3%) their levels ranged between (mild 9.1%, moderate 16.2%, severe 5%, extremely severe 2.7%), and different levels of psychological stress among about two thirds of a sample (29.9%) their levels ranged between (mild 14.2%, moderate 9.4%, severe 4.8%, extremely severe 1.6%) The results also showed that (53.7%) of the sample had a level between potential and confirmed for symptoms of Post-traumatic stress disorder.